The Implementation of Hadrah Art Extracurricular Program to Enhance Qur’anic Learning Motivation among TPA Students in Lampung - Wahyu Hadi Wibowo; Mirnawati Dewi (Episteme: Jurnal Kajian Mahasiswa, 2025)
Many children today face difficulties in learning the Quran, mainly due to a lack of interest, which hampers knowledge retention. Interest is crucial in the learning process, and without it, students struggle to absorb information. To address this issue, Raudlatul 'Ulum Al-Qur'an Education Park implemented an extracurricular program to foster greater engagement and enthusiasm for learning. This research investigates the background, implementation, and impact of these activities. Using a qualitative case study approach, data were collected through observations, interviews, and documentation. The findings reveal that extracurricular activities, held on weekends and in line with the institution’s mission, effectively increased students’ interest in learning. This resulted in greater enthusiasm and diligence, helping students overcome initial boredom and laziness, while improving their Quran recitation and learning experience.